Biceps Femoris Compensates for Semitendinosus After Anterior Cruciate Ligament Reconstruction With a Hamstring Autograft: A Muscle Functional Magnetic Resonance Imaging Study in Male Soccer Players. Issue 6 (May 2021) - Tampere, Thomas; Victor, Jan; Luyckx, Thomas; Vermue, Hannes; Arnout, Nele; Witvrouw, Erik; Schuermans, Joke
Background: Rates of reinjury, return to play (RTP) at the preinjury level, and hamstring strain injuries in male soccer players after anterior cruciate ligament reconstruction (ACLR) remain unsatisfactory, due to multifactorial causes. Recent insights on intramuscular hamstring coordination revealed the semitendinosus (ST) to be of crucial importance for hamstring functioning, especially during heavy eccentric hamstring loading. Scientific evidence on the consequences of ST tendon harvest for ACLR is scarce and inconsistent. This study intended to investigate the repercussions of ST harvest for ACLR on hamstring muscle function. Hypothesis: Harvest of the ST tendon for ACLR was expected to have a significant influence on hamstring muscle activation patterns during eccentric exercises, evaluated at RTP in a population of male soccer athletes. Study Design: Controlled laboratory study. Methods: A total of 30 male soccer players with a history of ACLR who were cleared for RTP and 30 healthy controls were allocated to this study during the 2018-2019 soccer season. The influence of ACLR on hamstring muscle activation patterns was assessed by comparing the change in T2 relaxation times [ΔT2 (%) =post − exercise − T 2 pre − exercise T 2 pre − exercise ] of the hamstring muscle tissue before and after an eccentric hamstring loading task between athletes with and without a recent history of ACLR through use of muscle functional magnetic resonance imaging, induced by an eccentric hamstring loading task between scans. Results: Significantly higher exercise-related activity was observed in the biceps femoris (BF) of athletes after ACLR compared with uninjured control athletes (13.92% vs 8.48%; P = .003), whereas the ST had significantly lower activity (19.97% vs 25.32%; P = .049). Significant differences were also established in a within-group comparison of the operated versus the contralateral leg in the ACLR group (operated vs nonoperated leg: 14.54% vs 11.63% for BF [ P = .000], 17.31% vs 22.37% for ST [ P = .000], and 15.64% vs 13.54% for semimembranosus [SM] [ P = .014]). Neither the muscle activity of SM and gracilis muscles nor total posterior thigh muscle activity (sum of exercise-related ΔT2 of the BF, ST, and SM muscles) presented any differences in individuals who had undergone ACLR with an ST tendon autograft compared with healthy controls. Conclusion: These findings indicate that ACLR with a ST tendon autograft might notably influence the function of the hamstring muscles and, in particular, their hierarchic dimensions under fatiguing loading circumstances, with increases in relative BF activity contribution and decreases in relative ST activity after ACLR. This between-group difference in hamstring muscle activation pattern suggests that the BF partly compensates for deficient ST function in eccentric loading. These alterations might have implications for athletic performance and injury risk and should probably be considered in rehabilitation and hamstring injury prevention after ACLR with a ST tendon autograft.